The efficacy of balance training in a Churg-Strauss Syndrome patient: a case report - Pistone, Giorgio; Camilli, Sabrina (Journal of Biomedical Practitioners, 2023)
INTRODUCTION Churg-Strauss Syndrome is a rare small-vessel vasculitis associated with asthma, blood and tissue eosinophilia. Peripheral neuropathy is reported in more than 50% of cases of Churg-Strauss Syndrome and it is often found related to motor and functional recovery issues. The Sensory system plays a key role in balance control, and that is why patients with polyneuropathy experience balance impairment during stance and gait. Impairments in gait and balance are two of the main causes of the falls characterizing Churg-Strauss syndrome. Evidence suggests that exercise programs can effectively improve gait and balance and reduce falls and fall-related injuries. The purpose of this paper is to show the importance of balance focused physiotherapy interventions to provide the best functional recovery to Churg-Strauss Syndrome patients. To date, the most recent literature does not provide us with evidence focusing on rehabilitation and physiotherapy in those patients. CASE PRESENTATION A 65-year-old male affected by Churg-Strauss Syndrome was referred to our inpatient rehabilitation ward one month after the onset of symptoms. Balance and gait were assessed using Berg Balance Scale, Mini-BESTest together with Tinetti Mobility Test. The rehabilitation protocol was designed to focus on balance and proprioception training and was performed for 2 months, 5 sessions of 90 minutes/week. After one month 15 minutes of balance training with visual biofeedback using Biodex Balance System SD were included in the balance training sessions. RESULTS we performed 4 testing sessions at four different times: baseline (T0), one month after the beginning of training (T1), 2 months later the beginning (T2) and 6 months follow-up (T3). Berg Balance Scale values moved from 8 at baseline assessment to 50 at follow up assessment. Score on the Mini-BESTest showed an increase from 2 points at T0 to 24 points at T3. Tinetti Mobility Score values improved from 11 points at T0 to 24 points at T3. DISCUSSION Scores on the Berg Balance Scale, Mini-BESTest and Tinetti Mobility Test showed significant improvements on all the 4 testing sessions. CONCLUSIONS it can be thus said that rehabilitation programs focusing on balance training constitute a reliable enhancement for functional outcomes in patients affected by Churg-Strauss Syndrome. Nonetheless, further investigation on physiotherapy strategies is needed.